William Desmond's Philosophy between Metaphysics, Religion, Ethics, and Aesthetics Thinking Metaxologically (Springer International Publishing, 2018)
This volume collects seventeen new essays by well-established and junior scholars on the philosophical relevance of metaxological philosophy and its main proponent, William Desmond. The volume mines metaxological thought for its salience in contemporary discussions in Continental philosophy, specifically in the fields of metaphysics, philosophy of religion, ethics, and aesthetics. Among others, topics under discussion include the goodness of being, the existence and nature of God, and the aesthetic dimensions of human becoming. Interest in metaxological philosophy has been on the rise in recent years, and this volume provides both a practical introduction and thorough engagements with it by experts in the field. The volume concludes with a series of responses by William Desmond on the issues raised by the contributors.